Mutational analysis of minichromosome maintenance complex component (MCM) family genes in Chinese Han women with polycystic ovarian syndrome - Jiangyan Zhou; Faying Liu; Lifeng Tian; Ming Yang; Jun Tan; Xianxian Liu; Peishuang Li; Jia Chen; Ge Chen; Lixian Xu; Lisha Peng; Qiongfang Wu; et al. (Taylor & Francis Group, 2023)
Purpose To investigate whether mutations in the minichromosome maintenance complex component (MCM) family genes were present in patients with polycystic ovary syndrome (PCOS) of Chinese descent.Methods A total of 365 Chinese patients with PCOS and 860 women without PCOS as control who underwent with assisted reproductive technology were enrolled. Genomic DNA was extracted from the peripheral blood of these patients for PCR and Sanger sequencing. The potential damage of these mutations/rare variants was analyzed through evolutionary conservation analysis and bioinformatic programs.Results Twenty-nine missense or nonsense mutations/rare variants in the MCM genes were identified in 365 patients with PCOS (7.9%, 29/365), all these mutations/rare variants were predicted to be 'disease causing' by SIFT and PolyPhen2 programs. Among those, four mutations were reported here for the first time, p.S7C (c.20C > G) in MCM2 (NM_004526.3), p.K350R (c.1049A > G) in MCM5 (NM_006739.3), p.K283N (c.849G > T) in MCM10 (NM_182751.2), and p.S1708F (c.5123C > T) in MCM3AP (NM_003906.4). All of these novel mutations were not found in our 860 control women, or also absent in public databases. In addition, the evolutionary conservation analysis results suggested that these novel mutations caused highly conserved amino acid substitutions among 10 vertebrate species.Conclusion This study identified a high frequency of potential pathogenic rare variants/mutations in MCM family genes in Chinese women with PCOS, which further expands the genotype spectrum in PCOS.